Les fonctions de la critique dans la sociologie de Pierre Bourdieu - Claude Gautier (Astérion)
The aim of this article is to restore the complexity and multiplicity of the functions of critique in Pierre Bourdieu’s sociology. The first function is a theoretical and scientific one that allows a Bachelardian-type of epistemological breakdown to be conducted. The second is a self-reflexive function that enables the objectivation of the knowing subject by making him aware of the epistemic (and partly social) privileges of his condition as a scholar. Only in this context does it become possible to consider the relationship of such sociology to social criticism, that also emerges as a moral and political duty. However, this dimension is not, as is often claimed, a militant posture of denunciation. On the contrary, it presupposes the satisfaction of conditions that make sociology a science. We will consider one of the possible forms of this dimension of social criticism which can make the sociologist a spokesperson.